The Risk Factors Contributing to The Occurrence of Pulmonary Tuberculosis in The Small Island of South Sulawesi, Indonesia - Susilawaty, Andi; Basri, Syahrul; Haerana, Bs Titi; La Ane, Ruslan; Mappau, Zrimurti; Ikhtiar, Muhammad (Public Health of Indonesia, 2024)
Background:Pulmonary tuberculosis (PTB) has emerged as the leading cause of death among infectious diseases globally. This is attributed to a complex interaction of factors, including host-related risk factors, infecting agents, and environmental conditions. The Southeast Asia and West Pacific regions account for 58% of all tuberculosis cases, with Indonesia reporting the second highest prevalence of tuberculosis globally (10%), following India, which accounts for 23% of global cases. Objective:This study aimed to investigate the risk factors associated with the incidence of pulmonary tuberculosis on small islands in South Sulawesi, Indonesia. Methods:This research employed a case-control study design. Several explanatory variables were considered: age, gender, knowledge, nutritional status, occupant density, ventilation area, humidity levels, and type of flooring. The occurrence of pulmonary tuberculosis was designated as the dependent variable. The study sample consisted of 240 respondents, with 120 cases and 120 controls, all residing on three small islands—Sembilan Island, Balang Lompo Island, and Salemo Island—all sharing similar characteristics. Results:The study identified several factors associated with an increased risk of pulmonary tuberculosis. These factors included gender (OR = 1.71, 95% CI 0.61-4.77), knowledge (OR = 3.143, 95% CI 1.06-9.26), occupant density (OR = 1.52, 95% CI 0.42-5.47), area of ventilation (OR = 6.00, 95% CI 1.17-30.72), humidity (OR = 3.763, 95% CI 1.03-13.64), and type of floor (OR = 1.144, 95% CI 0.41-3.16). In contrast, age and nutritional status were not identified as risk factors for pulmonary tuberculosis. Conclusion:Environmental factors such as occupant density, area of ventilation, humidity, and type of floor were found to be significant risk factors for the incidence of pulmonary tuberculosis in small islands of South Sulawesi. These findings highlight the need for targeted interventions addressing these modifiable environmental conditions to reduce the burden of tuberculosis. Keywords:risk factors; incidence; pulmonary tuberculosis; nutritional status; environmental factors; Indonesia